Penerapan Model UTAUT 2 (Unified Theory of Acceptance and Use of Technology 2) untuk Menganalisis Faktor – Faktor yang Mempengaruhi Intention to Use Seller dalam Menggunakan Fitur Invoice Financing di Platform Padi UMKM - Haekal Fikri Safdeni; Roni Faslah; Rayi Dwipanilih (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of Effort Expectancy, Social Influence, Facilitating Conditions, Price Value, and Habit on sellers' Intention to Use the Invoice Financing feature on the PaDi UMKM platform. Invoice Financing is a financing service that enables sellers to obtain working capital by receiving early payments based on transaction invoices. However, the utilization of this feature remains relatively low, making it necessary to identify the factors influencing sellers' intention to use the service. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to eligible PaDi UMKM sellers and analyzed using Statistical Package for the Social Sciences (SPSS) version 31, including data quality tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results indicate that Effort Expectancy, Social Influence, Facilitating Conditions, Price Value, and Habit have positive and significant effects, both individually and simultaneously, on sellers' Intention to Use the Invoice Financing feature. These findings suggest that ease of use, social support, adequate facilitating conditions, perceived value, and users' digital habits play important roles in encouraging sellers to adopt the financing service. The findings are expected to provide valuable insights for PaDi UMKM in developing strategies to increase the adoption of the Invoice Financing feature and to serve as a reference for future studies on technology adoption in digital financial services.